Changes in countermovement jump and sprint during a congested match schedule in female youth soccer players - Spalding, J. (East Tennessee State University, 2020)
Youth soccer players are required to play multiple matches within a short period of time. Participation in congested match schedules like youth soccer tournaments can result in fatigue and a decline in physical performance. The purpose of this study was to examine changes in countermovement jump height variables and sprint time to determine if physical performance was altered. Fourteen youth female soccer players performed countermovement jump testing pre, post-match, and post-tournament, and sprint testing pre and post-tournament. Jump height differed significantly (p <0.001) between time periods during the tournament, and sprint time increased by a statically significant amount (p = 0.001). Results also indicated that there were significant effects on CMJ variables; RSImod (p = 0.015), eccentric impulse (p = 0.022), concentric impulse (p = 0.010), peak power (p = 0.044). It was concluded that certain CMJ variables are sensitive to fatigue as well as sprint time and may be useful for coaches to use to monitor fatigue and determine recovery strategies and proper training load before and after a youth soccer tournament.